People engaged in opioid agonist treatment as a counterpublic during the COVID‐19 pandemic in Australia: A qualitative study. (31st August 2022) - Conway, Anna; Treloar, Carla; Crawford, Sione; Grebely, Jason; Marshall, Alison D.
Abstract: Introduction: People receiving opioid agonist treatment (OAT) are at higher risk of comorbidities, poverty and discrimination, which Big Events like the COVID‐19 pandemic may exacerbate. The behaviours of people receiving OAT do not always align with normative behaviours as conceived by ruling institutions and laws, and so the group becomes a counterpublic, not imagined in mainstream public discourse. The aim of this study was to understand how people receiving OAT, as a counterpublic, implemented practises of care to mitigate negative health outcomes during COVID‐19. Methods: Participants were recruited via eight peer‐led organisations across Australia. In‐depth, semi‐structured interviews were completed between August and December 2020 with 40 people receiving OAT. The analysis centres practises of care, allowing interactions that influence the health of participants, to be understood in their unique contexts. Results: Aspects of the COVID‐19 state response were designed for an idealised public, demonstrated by the increased policing that accompanied enforcement of restrictions which was detrimental to the wellbeing of people receiving OAT. Counterpublic health strategies employed by people receiving OAT were disrupted, but participants were often able to adapt to the changing context. Discussion and Conclusion: This study elucidates how practises of care among people receiving OAT are enacted and disrupted during a Big Event, with implications beyond the COVID‐19 pandemic for future Big Events. The study findings evidence the need for policies that mitigate the impact of Big Events such as supporting re‐groupment within the counterpublic, legitimising counterpublic health strategies and stopping the criminalisation of people who use drugs.